2012
DOI: 10.1002/em.21744
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic damage in open‐cast coal mine workers using the buccal micronucleus cytome assay

Abstract: Coal is the largest fossil fuel source used for the generation of energy. However, coal extraction and its use constitute important pollution factors; thus, risk characterization and estimation are extremely important for the safety of coal workers and the environment. Candiota is located to the southeast of the state of Rio Grande do Sul and has the largest coal reserves in Brazil, and the largest thermal power complex in the state. In the open-cast mines, the coal miners are constantly exposed to coal dust. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 38 publications
(42 reference statements)
4
11
0
3
Order By: Relevance
“…Two workers had confirmed (diagnosed) and three suspect pneumoconiosis, while the remaining 49 workers frequencies. These findings are in line with earlier reports of increased DNA damage in coal workers from different countries (7,8,(21)(22)(23)(24)(25)(26)(27) and contribute to the limited knowledge about the genotoxic effects of coal dust exposure in Turkish coal miners. One Turkish study (7) with 39 coal workers from the Armutcuk coal mine in the Zonguldak region found significantly higher sister chromatid exchange (SCE), chromosome aberration (CA), and MN frequencies in miners than controls.…”
Section: Chest X-ray and Spirometry Findingssupporting
confidence: 91%
“…Two workers had confirmed (diagnosed) and three suspect pneumoconiosis, while the remaining 49 workers frequencies. These findings are in line with earlier reports of increased DNA damage in coal workers from different countries (7,8,(21)(22)(23)(24)(25)(26)(27) and contribute to the limited knowledge about the genotoxic effects of coal dust exposure in Turkish coal miners. One Turkish study (7) with 39 coal workers from the Armutcuk coal mine in the Zonguldak region found significantly higher sister chromatid exchange (SCE), chromosome aberration (CA), and MN frequencies in miners than controls.…”
Section: Chest X-ray and Spirometry Findingssupporting
confidence: 91%
“…Many studies report a statistically significant elevation of MN levels in exposed individuals compared to control groups [45, 5456], and many other studies report changes that were not statistically significant [57, 58]. In this study, anomalous cell (MN and BN) frequencies of cases of buccal mucosa were mostly significantly higher than those of controls for participants occupationally exposed (Table 5).…”
Section: Discussionmentioning
confidence: 49%
“…It should be noted that most of the works devoted to the study of genotoxic effects using the BMCyt assay in miners are related to coal mining [54,68,69,85,86]. In these works, the authors showed a significant increase in the frequency of MN in buccal epithelium cells in coal miners.…”
Section: Discussionmentioning
confidence: 98%